Review. Applications of whey and its proteins derivatives (2023)
Abstract Whey was discovered about 3,000 years ago as a by-product of the dairy industry (mainly cheese) and for years it was considered a liquid waste, used as animal feed or simply dumped into rivers. However, today the use of whey allows it to be recognized as a nutritional ingredient with high added value applied to many food products. Within its composition we find: lactose, fat, proteins of important biological value, minerals and vitamins; whey proteins constitute an economic source with multiple techno-functional, nutraceutical and nutritional properties, useful to add to a wide range of foods, multiplying development possibilities for the dairy industry itself. Taking into account the above, throughout this review relevant aspects of this dairy by-product will be described, emphasizing the proteins that make it up and their derivatives (concentrated and hydrolyzed), as well as the molecular, physicochemical and functional properties, aspects that they position it as a striking raw material at an industrial level in addition to the benefits it imparts to the health of the consumer.